The Non-Coalescence of /h/ and Incomplete Neutralization in South Jeolla Korean. (June 2023) - J. Lee, Seunghun; Villegas, Julián; Oh, Mira
This study examines articulatory and acoustic data in order to investigate the non-coalescence of /h/ in South Jeolla. Seoul Korean speakers produce /pap/ "rice" followed by /hana/ "one" as [pa.p h a.na] with the coalescence of /p/ and /h/; this is called an aspiration merger. In South Jeolla Korean, this merger may be blocked, as in cases where speakers produce /pap+hana/ as [pa.b a.na]. Electroglottographic (EGG) data indicate the existence of two groups of South Jeolla speakers: one that merges the plosive and /h/ (the merger group), and the other with the canonical South Jeolla Korean pronunciation that does not merge the two consonants (the non-merger group). The production of non-coalesced lenis stops in the non-merger group is phonetically comparable with an underlying lenis stop produced by both of the groups. However, in the non-merger group, the open quotient (OQ) of a vowel following a non-coalesced lenis stop is higher (breathier) than that of an underlying lenis stop. Spectral tilt results display a similarly increased breathiness when the vowel follows a non-coalesced lenis stop. As for the non-merger group of South Jeolla, we argue that speakers display incomplete neutralization such that the non-merger group produces two types of voiced lenis stops differing in the phonation of the following vowel. These findings suggest that previous phonological analyses that posit the /h/-deletion in the non-merger group of South Jeolla Korean need to be revisited.